Measuring Airway Obstruction in Severe Asthma in Children - Calogero, Claudia; Fenu, Grazia; Lombardi, Enrico (Frontiers in Pediatrics, 2018)
Lung function is an important tool in the diagnosis and monitoring of patients with asthma at all age. Airway obstruction is a typical feature of asthma and it can be assessed with several lung function techniques. Spirometry, respiratory resistance and reactance, and lung volumes are available to measure it at different ages and in children. The assessment of a bronchodilator response is always recommended to show the reversibility of the obstruction. Poor lung function value is a predictor of poor asthma outcome and a low Forced Expiratory Volume in the first second of expiration percent predicted measured with spirometry, has been shown to be associated with a higher risk of having an exacerbation during the following year independently of the presence of symptoms of asthma or not. In severe asthma lung function assessment is used to distinguish different phenotypes, children with severe asthma have worse airflow limitation prior to administration of a bronchodilator than children with non severe asthma. Airway resistance and reactance are indirect measurements of airway obstruction and they can be measured with the forced oscillation technique, which is feasible also in non-collaborative children. This technique can be more informative in discriminating patients with asthma from healthy controls and is able to indicate a more peripheral involvement of the airways. The role of this technique in severe asthma is still debated. In conclusion lung function is useful in the clinical management of children with severe asthma.